Detection of movie violence using motion intensity analysis on skin and blood (DOVE) - Clarin, Christine T. (2005)
DOVE is an automated system which detects violence in motion pictures. It accepts an MPEG stream converted from a VCD file. Many violent movies are widely distributed, a concern has been raised among mature audiences who want to regulate the amount and degree of violence children see on movies. Addressing this concern is DOVE which is useful to the older generation as a way to automate scanning of violent scenes before actually letting children see the whole film. Consequently, DOVE cam also be employed for other applications not just for home use but also for purposes of commercialization, etc. However, the degree of violence is vast and subjective and so in this system, violence is clearly defined as movie sequences involving actions producing blood like extreme punching, kicking, stabbing, and other acts as such. To describe this type of violence in context of image processing is difficult and has to be precise therefore, DOVE uses three filters in order to accurately differentiate violent motion from others. The first filter is that only active (fast moving) scenes within the movie are considered candidates for violence. Following film making conventions, violence is found in fast sequences in order to emphasize motion, thus exciting the audience. The second and third filters concentrate on the presence of skin and blood and the intensity of their movement along each of the sequences of the movie. The reason for this is that most violent films highlight the occurrence of blood from skin wounds as result of extreme violence. The regions where the isolated skin and blood are located are then measured for motion intensity, if they were indeed the regions moving fast, then the system concludes that a violent action is happening and thus declares that scene violent.